Facing the Missile Challenge U.S. Strategy and the Future of the INF Treaty - Kearn, David W. Jr (RAND Corporation, 2012)
Report assesses whether the Intermediate Nuclear Forces Treaty continues to serve America's national interests, or whether adherence unduly constrains the U.S. ability to effectively respond to emerging security threats. Analyzes challenges confronting the United States from Iran, North Korea, India, Pakistan, and China, and considers the potential role of a future U.S. land-based, intermediate-range conventional ballistic missile system.